ILMUAN-ILMUAN MUSLIM KLASIK: PELOPOR SAINS MODERN - M. Azhar Fauzan; Siti Ainul Hayat (PT. Saha Kreasi Indonesia, 2026)
This study discusses the role of classical Muslim scholars as pioneers of modern science during the Islamic Golden Age (8th to 14th centuries CE). The method used is library research with a historical-factual approach and descriptive-qualitative analysis. The results show that figures such as Al-Khawarizmi (mathematics, algorithms), Ibn Sina (medicine, Canon of Medicine), Ibn al-Haytham (optics, experimental method), Al-Biruni (astronomy, geography), Jabir ibn Hayyan (chemistry, distillation), and Al-Jazari (engineering, automation) not only preserved ancient knowledge but also developed it through systematic observation, laboratory experimentation, and scientific documentation. Their contributions became the foundation for various modern scientific disciplines such as algebra, algorithms, the scientific method, optics, pharmacology, and mechanical engineering. In conclusion, classical Muslim scholars served as a bridge between ancient knowledge and the European Scientific Revolution, and their thoughts remain relevant in STEM education and contemporary technological developments such as artificial intelligence, robotics, and nanomaterials.